Efficacy and safety of a centrally acting analgesic flupirtine in primary knee osteoarthritis in comparison to tramadol: a randomized controlled trial - Goswami, Tanmoy Kanti; Ghoshal, Pradip Kumar; Hazra, Avijit; Biswas, Asish (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Osteoarthritis (OA) is a chronic, degenerative joint disorder responsible for considerable morbidity, particularly in old age. Flupirtine, a new centrally acting analgesic, is devoid of the adverse effects of NSAIDs and opioid analgesics. In this study author compared the effectiveness and safety of flupirtine with tramadol in knee OA. Methods: An open label, randomized, controlled trial was done with patients of primary knee OA of both sexes, age >50 years. Patients were recruited from Rheumatology OPD of SSKM Hospital. A minimum WOMAC score of 35 was essential for recruitment. Patients with serious comorbidities were excluded. They were treated orally with either flupirtine (100mg thrice daily) or tramadol (50mg thrice daily) for 12 weeks. Results: Ninety patients were recruited and data of 42 on flupirtine and 41 on tramadol were analysed. There was significant improvement in pain, stiffness and physical function compared to baseline in both the groups. However, there was no significant difference between groups at 4, 8 and 12 weeks. Responder rate (50% reduction in pain score from baseline) was 66.67% with flupirtine and 48.78% with tramadol (p = 0.122). Flupirtine caused 4 adverse events compared to 16 with tramadol. However, both the drugs were well-tolerated. Conclusions: The effectiveness of flupirtine in knee OA is comparable to tramadol, while causing minimal adverse effects. Long-term benefits need to be explored.